KnowledgeBoat Logo

Mathematics

The angle of elevation of a cloud from a point h metres above the surface of a lake is θ and the angle of depression of its reflection in the lake is Φ. Prove that the height of the cloud above the lake surface is : h(tan Φ + tan θtan Φ - tan θ)h\Big(\dfrac{\text{tan Φ + tan θ}}{\text{tan Φ - tan θ}}\Big).

Heights & Distances

3 Likes

Answer

In the figure shown below:

The angle of elevation of a cloud from a point h metres above the surface of a lake is θ and the angle of depression of its reflection in the lake is Φ. Prove that the height of the cloud above the lake surface is : h = (tan Φ + tan θ)/(tan Φ - tan θ). Model Paper 4, Concise Mathematics Solutions ICSE Class 10.

Let BQ be the surface of lake, P be the cloud and R be its reflection in lake.

Let H metres be the height of the cloud above water level. The distance of the reflection is same as that of the cloud from the lake surface.

PQ = QR = H meters

Let A be the point h meters above the surface of the lake from where angle of elevation is θ.

Let AB = h metres, AC = BQ = x

In △ACP,

tan θ = PCAC\dfrac{PC}{AC}

Substituting values we get :

tan θ=Hhxx=Hhtan θ …….. (1)\Rightarrow \text{tan θ} = \dfrac{H- h}{x} \\[1em] \Rightarrow x = \dfrac{H - h}{\text{tan θ}} \text{ …….. (1)}

tan Φ = RCAC\dfrac{RC}{AC}

Substituting values we get :

tan Φ=H+hxx=H+htan Φ …….. (2)\Rightarrow \text{tan Φ} = \dfrac{H + h}{x} \\[1em] \Rightarrow x = \dfrac{H + h}{\text{tan Φ}} \text{ …….. (2)}

From (1) and (2), we have :

Hhtan θ=H+htan Φ(Hh) tan Φ=(H+h) tan θH tan Φ - h tan Φ=H tan θ + h tan θH tan Φ - H tan θ=h tan θ + h tan ΦH(tan Φ - tan θ)=h(tan θ + tan Φ)H=h(tan θ + tan Φ)(tan Φ - tan θ).\Rightarrow \dfrac{H - h}{\text{tan θ}} = \dfrac{H + h}{\text{tan Φ}} \\[1em] \Rightarrow (H - h)\text{ tan Φ} = (H + h)\text{ tan θ} \\[1em] \Rightarrow \text{H tan Φ - h tan Φ} = \text{H tan θ + h tan θ} \\[1em] \Rightarrow \text{H tan Φ - H tan θ} = \text{h tan θ + h tan Φ} \\[1em] \Rightarrow H\text{(tan Φ - tan θ)} = h\text{(tan θ + tan Φ)} \\[1em] \Rightarrow H = \text{h}\dfrac{\text{(tan θ + tan Φ)}}{\text{(tan Φ - tan θ)}}.

Hence, proved that the height of the cloud above the lake surface is h(tan Φ + tan θtan Φ - tan θ)h\Big(\dfrac{\text{tan Φ + tan θ}}{\text{tan Φ - tan θ}}\Big).

Answered By

3 Likes


Related Questions